Predicting Cherax quadricarinatus Habitat Distribution Patterns Through the Usage of GIS and eDNA Analysis in Terengganu, Malaysia - Mohamad Zulkarnain, Mohd Dali; Muhammad Syafiq, Aiman Mohd Nasir; Khaleel, Aliyu Garba; Chun, Leong Mun; Gan, Han Ming *; Nik Ahmad, Firdaus Nik Wan; Roslan, Umar; Ahmad Syazni, Kamarudin (Universiti Kebangsaan Malaysia, 2023)
Cherax quadricarinatus (von Martens, 1868) is a highly invasive species that is resilient and highly adaptable to environmental conditions in new locations. Its presence brings along ecosystem imbalances and causes socioeconomic losses in invaded areas. Due to the destructive behaviour, it is important to conduct preliminary assessment methods and scientific studies especially on its behavioural and dispersal patterns. Thus, this study aims to determine the habitat distribution patterns of C. quadricarinatus based on the methods of GIS and environmental DNA (eDNA) analysis. The study was done at Felda Tenang, Terengganu, Malaysia. Based on the geographical features and climate conditions of the study area, we theorized that there are fewer and older C. quadricarinatus present at higher areas but more and younger C. quadricarinatus at lower areas. We found that 91.67% of the study area to be invaded, thus imploring the need for future mitigation plans to curb their dispersal into new areas. Future studies should also be done to determine the habitat distribution patterns of C. quadricarinatus in other areas.